2018
DOI: 10.2147/cmar.s168610
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of lenalidomide for the treatment of acute myeloid leukemia: a systematic review and meta-analysis

Abstract: BackgroundLenalidomide is effective for the treatment of low-risk myelodysplastic syndromes with deletion 5q abnormalities. However, whether lenalidomide leads to a significant improvement in treatment response and overall survival (OS) in cases of acute myeloid leukemia (AML) remains controversial. A systematic review and a meta-analysis were performed to evaluate the efficacy and safety of lenalidomide in the treatment of AML.MethodsClinical studies were identified from the Cochrane Central Register of Contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Probably, the most significant results occur following two combination therapies—lenalidomide plus cytarabine and lenalidomide plus 5-AZA, suggesting a possible synergic action of these molecules. The most important studies reported a response rate of approximately 30% for these two combinations [ 31 ]. It was shown that the cytogenetic risk had exerted only a minimal impact on the outcomes of lenalidomide-based regimens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Probably, the most significant results occur following two combination therapies—lenalidomide plus cytarabine and lenalidomide plus 5-AZA, suggesting a possible synergic action of these molecules. The most important studies reported a response rate of approximately 30% for these two combinations [ 31 ]. It was shown that the cytogenetic risk had exerted only a minimal impact on the outcomes of lenalidomide-based regimens.…”
Section: Discussionmentioning
confidence: 99%
“…The use of lenalidomide in studies reported in literature is generally in a particular subset of AML patients—untreated elderly patients, poor cytogenetic risk or R/R patients. A meta-analysis and systematic review by Chun-Hong Xie et al [ 31 ] reported that in AML patients treated with lenalidomide as monotherapy, the CR rate was relatively low (14%) and the ORR was 22%. In a phase 2 study by Fehniger et al [ 32 ], untreated AML patients aged 60 years or more (median age, 71 years) received high dose (HD) lenalidomide (50 mg/day) for up to two 28-day-cycles.…”
Section: Lenalidomidementioning
confidence: 99%
See 2 more Smart Citations
“…A modified version of the Newcastle-Ottawa Scale for cohort studies was used to assess the quality of studies 19,20. The quality and risk of bias for all eligible papers in this systematic review were evaluated independently by two investigators.…”
Section: Methodsmentioning
confidence: 99%